2005
DOI: 10.1139/f04-147
|View full text |Cite
|
Sign up to set email alerts
|

Late-season mortality during migration of radio-tagged adult sockeye salmon (Oncorhynchus nerka) in the Columbia River

Abstract: We radio-tagged 577 adult sockeye salmon (Oncorhynchus nerka) returning to the Columbia River in 1997 to determine how migration behaviors were related to migration success in an altered river system. The probability of successful migration declined dramatically for late-entry individuals, concomitant with declines in discharge and the onset of stressful temperatures. Long dam passage times were not related to unsuccessful migration at most dams. However, when migration histories were analyzed across multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 39 publications
5
115
1
Order By: Relevance
“…However, the fact that median dates have remained relatively unchanged suggests that, on average, this run has probably been exposed to increasingly warmer water temperatures over time. The implications of this for survival, energetic demands, and gamete development are unclear, though exposure to high temperatures during migration has been associated with elevated bioenergetic depletion and prespawn mortality (Gilhousen 1990;Cooke et al 2004;Naughton et al 2005;Richter and Kolmes 2005) and lowered fertility (Flett et al 1996;King et al 2003) in other salmon runs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that median dates have remained relatively unchanged suggests that, on average, this run has probably been exposed to increasingly warmer water temperatures over time. The implications of this for survival, energetic demands, and gamete development are unclear, though exposure to high temperatures during migration has been associated with elevated bioenergetic depletion and prespawn mortality (Gilhousen 1990;Cooke et al 2004;Naughton et al 2005;Richter and Kolmes 2005) and lowered fertility (Flett et al 1996;King et al 2003) in other salmon runs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown successful migrants (i.e. individuals which reached spawning grounds) had lower approach and passage times at obstacles when compared with unsuccessful individuals Naughton et al, 2005;Lundqvist et al, 2008;Makiguchi et al, 2011), suggesting potentially rapid obstacle passage reduces energetic costs in barrier passage resulting in greater success of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Passage time at dams along the Columbia and Snake rivers have been strongly related to time of day as migrant salmon have been observed to overnight in the tailrace prior to passage (Naughton et al 2005;Caudill et al 2007). However, this did not appear to explain the difference in passage times we observed at Seton Dam as there was no difference in release times among the three discharge periods.…”
Section: Discussionmentioning
confidence: 99%
“…Because time of day can affect passage rates at dams (Naughton et al 2005), we compared release times of tagged fish among the discharge periods using a Wilcoxon-Kruskal-Wallis test, and conducted a Spearman's rank correlation analysis between release time of day and passage time. Passage times, which were normally distributed under each discharge period (Kolmogorov-Smirnov test; all P .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation